2021
DOI: 10.3389/fphar.2021.732630
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Inflammation, Oxidative Stress, and Vascular Impairment Is Ablated in Diabetic Mice Receiving XMD8-92 Treatment

Abstract: The global number of diabetics continues to rise annually. As diabetes progresses, almost all of Type I and more than half of Type II diabetics develop diabetic retinopathy. Diabetic retinopathy is a microvascular disease of the retina, and is the leading cause of blindness in the working-age population worldwide. With such a significant health impact, new drugs are required to halt the blinding threat posed by this visual disorder. The cause of diabetic retinopathy is multifactorial, and an optimal therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…A previous study in diabetic mice showed that BRD4 induces retinal inflammation and plays a role in retinal degeneration. 48 Adiponectin downregulates BRD4 kinase activity, which could suppress the inflammatory process and angiogenesis functions.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in diabetic mice showed that BRD4 induces retinal inflammation and plays a role in retinal degeneration. 48 Adiponectin downregulates BRD4 kinase activity, which could suppress the inflammatory process and angiogenesis functions.…”
Section: Discussionmentioning
confidence: 99%
“…111 Additionally, while there is evidence of increased MAP kinase signaling in ALS patients as well as in animal and iPSC models, 57,[112][113][114][115] two compounds identified here were MAP kinase inhibitors (XMD-892, XMD-885). Finally, XMD-892 116 and other compounds (tacedinaline, [117][118][119] MLN4924, 120 piperlongumine, 121,122 prunetin 123 ) have also been under investigation for their antioxidant, anti-inflammatory, anti-ischemic, neuroprotective, and/or antitumour properties.…”
Section: Discussionmentioning
confidence: 99%
“…Acellular capillaries were quantified in the retinal vasculature as previously described [ 18 , 19 , 20 , 21 ]. Eyes were fixed with 10% formalin.…”
Section: Methodsmentioning
confidence: 99%
“…After IL-17A binds to IL-17R, Act1-TRAF (TNF receptor associated factor) signaling cascades then activate NF-κB-dependent inflammation, FADD-dependent endothelial cell death, and ERK5-dependent oxidative stress in the diabetic retina. This leads to retinal vascular impairment and the onset of non-proliferative diabetic retinopathy [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%